2009
DOI: 10.1118/1.3049787
|View full text |Cite
|
Sign up to set email alerts
|

Maximum proton kinetic energy and patient‐generated neutron fluence considerations in proton beam arc delivery radiation therapy

Abstract: Several compact proton accelerator systems for use in proton therapy have recently been proposed. Of paramount importance to the development of such an accelerator system is the maximum kinetic energy of protons, immediately prior to entry into the patient, that must be reached by the treatment system. The commonly used value for the maximum kinetic energy required for a medical proton accelerator is 250 MeV, but it has not been demonstrated that this energy is indeed necessary to treat all or most patients el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…Even though the distribution of neutrons throughout the patient anatomy might have differed slightly because of the different beam arrangement, this approximation provided a conservative estimate of the total neutron production for proton arc therapy, due to the larger number of neutrons created by the higher beam energy and the larger amount of tissue traversed for parallel-opposed beam proton therapy (Zheng et al 2008, Sengbusch et al 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Even though the distribution of neutrons throughout the patient anatomy might have differed slightly because of the different beam arrangement, this approximation provided a conservative estimate of the total neutron production for proton arc therapy, due to the larger number of neutrons created by the higher beam energy and the larger amount of tissue traversed for parallel-opposed beam proton therapy (Zheng et al 2008, Sengbusch et al 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Some of these are enumerated here, with an emphasis on those questions that will require physics research and development to reduce cost, improve treatment quality and efficiency, and create previously new treatment capabilities of clinical importance. Can novel techniques, such as proton arc therapy (Sandison et al , 1997; Sengbusch et al , 2009; Rechner et al , 2012), be developed to improve the quality of treatment, reduce treatment time, and increase cost-competitiveness and -effectiveness?Can cost-competitiveness or treatment capability be increased significantly through incremental improvements to existing accelerator technologies, e.g. , fixed-field alternating gradient synchrotron (Johnstone et al , 1999) and superconducting cyclotron accelerators (Blosser et al , 1997), or novel linear accelerators, e.g.…”
Section: Challenges and Future Of Proton Therapymentioning
confidence: 99%
“…Can novel techniques, such as proton arc therapy (Sandison et al , 1997; Sengbusch et al , 2009; Rechner et al , 2012), be developed to improve the quality of treatment, reduce treatment time, and increase cost-competitiveness and -effectiveness?…”
Section: Challenges and Future Of Proton Therapymentioning
confidence: 99%
“…Further, higher energy leads to increased secondary neutrons and radioactivity both in the gantry and in the patient. Using Monte Carlo simulation it was shown that the total neutron fluence increases with E 3.76 where E is proton beam energy (16), and a reduction in beam energy from 240 MeV to 200 MeV decreased the secondary neutron fluence by 2.3 folds from 3.5 3 10 23 to 1.5 3 10 23 neutrons/p. There is no actual need for higher energies except potentially for proton computed tomography.…”
Section: Discussionmentioning
confidence: 99%